1997
DOI: 10.1002/(sici)1099-0720(199702)11:1<55::aid-acp423>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive Interview and Lie Detection: a New Magnifying Glass for Sherlock Holmes?

Abstract: The observation of serious deficiencies in the traditional police interview led Geiselman and colleagues to develop an alternative method of questioning. This method is known as the cognitive interview. The CI starts from the premise that the witness, victim or suspect wishes to cooperate. But, what happens if this is not the case? More seriously, what happens if he/she lies? The main aim of this study is to examine the differences between true and false statements, as a function of the interview technique emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 21 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…Following earlier researchers (e.g., Hernandez‐Fernaud & Alonso‐Quecuty, 1997; Köhnken, Schimossek, Aschermann, & Höfer, 1995; Strömwall et al , 2004) a modified version of the CI was used to interview participants as this procedure typically results in a detailed recall (Köhnken, Milne, Memon, & Bull, 1999). Both interviewers received 2 days of intensive training in the CI which involved practice role‐plays with mock interviewees and extensive feedback.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following earlier researchers (e.g., Hernandez‐Fernaud & Alonso‐Quecuty, 1997; Köhnken, Schimossek, Aschermann, & Höfer, 1995; Strömwall et al , 2004) a modified version of the CI was used to interview participants as this procedure typically results in a detailed recall (Köhnken, Milne, Memon, & Bull, 1999). Both interviewers received 2 days of intensive training in the CI which involved practice role‐plays with mock interviewees and extensive feedback.…”
Section: Methodsmentioning
confidence: 99%
“…In this method, the phenomenal characteristics associated with the witness' memory report are extracted from the content of the report by independent trained evaluators or judges rather than being explicitly provided (rated) by the witness. Several studies have tested the diagnostic capacity of RM criteria derived in this manner in distinguishing accounts based on memory from those based on imagination (e.g., Barnier, Sharman, McKay, & Sporer, 2005; Hernandez‐Fernaud & Alonso‐Quecuty, 1997; Larsson & Granhag, 2005; see Masip, Sporer, Garrido, & Herrero, 2005; Roberts, Lamb, Zale, & Randall, 1998; Santtila, Roppola, & Niemi, 1999; Sporer, 1997; Strömwall, Bengtsson, Leander, & Granhag, 2004). The RM approach has been operationalized and studied in different laboratories each with overlapping criteria but with differences in their approach.…”
mentioning
confidence: 99%
“…However, in the second study, the accuracy rate of the additional information pertaining to the description of person was lower for the OD instruction than for the MR instruction. In previous studies, some authors have already observed an increase in the amount of incorrect information about persons with the CI (Hernandez-Fernaud & Alonso-Quecuty, 1997;Memon et al, 1994). This can be explained by the fact that this instruction leads interviewees to lower their own personal requirement for accuracy (Koriat, Goldsmith, & Pansky, 2000) and thus leads them to give less accurate details.…”
Section: Can the Open Depth Instruction Be An Efficient Additional Inmentioning
confidence: 95%
“…Observed in the studies by Landstrom and Garnhag (2005) was the fact that certain RM criteria (temporal, spatial information) emerge more often in false statements acquired in CI than in SI. In turn, no negative impact of CI on the presence of RM criteria was observed in Hernandez-Fernaud and Alonso-Quecuty (1997). Th e results of the studies quoted above point to the fact that a cognitive interview may have a bearing on the effi ciency of content-based techniques, yet this area has not been fully researched yet.…”
Section: Themselves Note This Processesmentioning
confidence: 99%